IbM MANAJEMEN PENGELOLAAN KEUANGAN LPD BERBANTUAN SIMPeDe - Wirawan, I Made Agus; Suwendra, I Wayan; Sugihartini, Nyoman (Universitas Pendidikan Ganesha, 2018)
LPD is the micro finance institution which aims to develop the economy of the rural communities, especially in Bali. This micro finance institution has been built in some places in Bali such as in Desa Adat Penatahan and Desa Adat Tangkas. However, there are some hindrances faced by those institutions, such as; (1) Unavailability of the computer infrastructure to support the financial operations, (2) Unavailability of qualified system/software in the transaction and financial management, and (3) The administrative and financial management skills of the officer are low.Based on the analysis of the situation and the problem above, the proposer's team offer some solutions: (1) Implementing hardware and Software SIMPeDe to support LPD financial transaction process. (2) Implementing SIMPeDe hardware and Software to support LPD financial transaction process. (3) Implementing SIMPeDe hardware and Software to support LPD financial transaction process.This training program is divided into several processes, namely: (1) Planning and preparation process which includes software installation. (2) The training for operating SIMPeDe. (3) Implementation of application to the customer and socialization to the community. (4) The evaluation process includes the evaluation of LPD performance and response of the community as a customer.